Impact of the design of adult mental health inpatient facilities on healthcare staff: a mixed methods systematic review - Joanne Kinloch; Laura Rodríguez-Labajos; Louise Nicol; Susan Grant; Geraldine O'Brien (BMJ Open)
Objectives Mental health inpatient facilities are increasingly focusing on creating therapeutic, person-centred care environments. However, research shows that this focus may have unintended consequences for healthcare staff. Designs that do not pay attention to staff needs may risk contributing to stress, burnout, job dissatisfaction and mental exhaustion in the work environment. This systematic review aims to identify and synthesise current research on the design factors of adult mental health inpatient facilities that impact healthcare staff.Design A mixed method systematic review was conducted to search for empirical, peer-reviewed studies using the databases CINAHL, Embase, PsycINFO, PubMed and Web of Science from their inception up to 5 September 2023. The Joanna Briggs Institute’s critical appraisal checklists were used to assess the methodological quality of the eligible studies. Data were extracted and grouped based on the facility design factors.Results In our review, we included 29 peer-reviewed empirical studies that identified crucial design factors impacting healthcare staff in adult mental health inpatient facilities. Key factors included layouts providing optimal visibility, designated work and respite areas, and centrally located nursing stations. Notably, mixed perceptions regarding the benefits and challenges of open and glass-enclosed nursing stations suggest areas requiring further research. Facilities in geographically remote locations also emerged as a factor influencing staff dynamics. Additionally, although only supported by a limited number of studies, the significance of artwork, sensory rooms for respite, appropriate furniture and equipment, and access to alarms was acknowledged as contributory factors.Conclusion Through the synthesis of existing research, this review identified that the design of mental health facilities significantly impacts staff well-being, satisfaction, performance and perception of safety. Concluding that, in order to create a well-designed therapeutic environment, it is essential to account for both service users and staff user needs.PROSPERO registration number CRD42022368155.